CYTOMEGALOVIRUS AND VIRUS EPSTEIN- BARR INFECTION IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND ITS DEPENDENCE ON GENDER AND AGE OF PATIENTS (World Science, 2020)
Introduction. Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by various manifestations and clinical course, many aspects of the etiology and pathogenesis of which remain unclear. Recently, the interest of researchers in studying the role of cytomegalovirus (CMV) and Epstein - Barr virus (EBV) has been growing in the occurrence and course of a number of human diseases due to their ability to affect almost all organs and systems of the body, causing the formation of latent, active or chronic infection, which can often cause temporary disability, disability or even death, however, for the patients with SLE, despite the possibility of approaching the difficult problem of diagnosis and treatment of this disease, this issue is given insufficient attention, as evidenced by isolated studies.The aim of the study. Detect cytomegalovirus and Epstein - Barr infection in patients with systemic lupus erythematosus and its dependence on gender and age of patients. Materials and methods of research. The study involved 120 patients (15 men (12.50%) and 105 women (87.50%) aged 18 to 69 years with SLE, who were in the rheumatology department of the Communal Non-Commercial Enterprise of the Lviv Regional Council "Lviv Regional Clinical Hospital" in 2014-2019. To diagnose CMV and EBV infection by enzyme-linked immunosorbent assay, antibodies of IgM and IgG to viruses were detected in blood serum, and viruses were detected by polymerase chain reaction. According to the results of virus detection, formed groups of the patients, namely: patients with active CMV infection, active EBV, active CMV and EBV, without active CMV and EBV. All patients with SLE included in the study were subsequently stratified by age according to the classification of the World Health Organization (2015), according to which the following age limits were determined: young age, middle-aged, elderly, senile. Statistical analysis was performed on a personal computer in MS Excel and Statistica 6.0 using descriptive statistics. The frequency of cases of active CMV and EBV infection was calculated mathematically by the binomial coefficient of I. Newton. Research results and their discussion. We found in the vast majority of patients with SLE (117 patients, 97.50%) increase in the titer of specific antibodies to CMV. Only in 3 patients (2.50%) the titer of antibodies to this virus was within normal limits. Analyzing the frequency of EBV infection in patients with SLE, we recorded an increase in the titer of specific antibodies to the virus in 119 patients (99.17%). Among the examined patients with SLE in all (100.00%) found an increase in the titer of antibodies to CMV and / or EBV, of which 97.50% - infected with CMV and 97.17% - infected with EBV. The active phase of CMV and / or EBV infection was detected in 54.17%, of which 23.33% - active CMV infection, 17.50% - active EBV infection and 12.50% - a combination of active CMV and EBV infection simultaneously, which indicates a high frequency of CMV and EBV infection in patients with SLE and reflects the urgency of the problem of diagnosing herpesvirus infection in them. We found that activeCMV, EBV infections and their combinations are present only in women (64 patients, which is 60.96% of the total number of women with SLE), of which 28 patients (26.67%) there was only active CMV infection, in 21 patients (20.00%) - only active EBV infection and in 15 patients (14.29%) – combination of active CMV and EBV infection. 41 women (39.05%) and all (100.00%) men were not found to have active CMV and EBV infection, which indicates that men at the time of the survey were significantly more likely to have this infection in the integration phase. The most frequently active EBV infection was detected in patients with SLE of young age (17 cases, 24.64%), and in middle-aged patients 3 cases (6.52%) were recorded, which indicates a significant (p